Pengaruh Modal Kerja Terhadap Penjualan Dan Laba Perusahaan (Studi Kasus pada Sektor Food and Beverage yang terdaftar di BEI 2011-2014) - Erlina Yunitasari Widyamukti; Junianto Wibowo (Universitas Katolik Soegijapranata, Semarang, 2018)
Working capital is very useful for a firm, mainly when it will operate its business like to purchase raw material, to pay salary and wages, etc. With certain working capital, a firm will be able to stipulate sales and to gain profit. This research is conducted for evaluation of influencing working capital on sales and profit separately. Samples of this research consist of 13 firms go public on food and beverage sector from 2011 until 2014. Data used is secondary data of financial report from those firms from 2011 until 2014. The data is obtained with documentary method, conducted by recording data needed from financial report of www.icamel.id. Then, these data are analyzed with simple regression analysis tehnique. The results showed that with a significance level 5%, independent variables net working capital affect the dependent variable, both sales and corporate profits.